MUSCULOSKELETAL DISORDERS AND PERCEPTION OF WORKING CONDITIONS: A SURVEY OF BRAZILIAN DENTISTS IN SAO PAULO - Isper Garbin, Artenio Jose [UNESP]; Soares, Gabriella Barreto [UNESP]; Arcieri, Renato Moreira [UNESP]; Saliba Garbin, Clea Adas [UNESP]; Siqueira, Carlos Eduardo (Nofer Inst Occupational Medicine, Sw, 2017)
Objectives: To investigate the prevalence of work-related musculoskeletal disorders amongst dentists who work in public clinics in Sao Paulo, Brazil, to investigate their awareness of the presence of risk factors in the workplace, disability due to pain, and the influence of pain on this awareness and disability. Material and Methods: A cross-sectional study was conducted among 204 dentists who work in public health clinics in the northwest of Sao Paulo, Brazil. The data was collected through interviews, using the Nordic Questionnaire and the Work-Related Activities that May Contribute to Job-Related Pain Questionnaire. In the case of workers who reported pain, the Pain Disability Questionnaire (PDQ) and the Numeric Pain Scale were also administered. Statistical analyses were performed using SPSS 21.0. Results: Most dentists (81.4%) had musculoskeletal disorders, especially in the neck, shoulders and lower back. We found that the presence of symptoms in the neck (15.7%), shoulders (12.7%) and lower back (15.7%) were the major causes of absenteeism over the past 12 months. Occupational risk factors perceived as the most problematic ones were: bending or twisting the back in an awkward way, continuing to work when injured or hurt and working in the same position for long periods. Comparison between the symptomatic and asymptomatic dentists showed a statistically significant difference (p < 0.05) in the perception of occupational risk factors. The analysis of the intensity of pain and disability with PDQ in the symptomatic dentists showed an average pain intensity of 3.8. Mean scores of the PDQ total (11.46) and its dimensions - functional condition (7.1) and psychosocial condition (4.4) - suggest a moderate disability in the dental surgeons. There was a strong t correlation (r = 0.697) between pain intensity and the total score of disability caused by pain. Conclusions: Pain and work-related musculoskeletal disorders interfere significantly with the dentists' lives. In the case of dental surgeons there is a significant correlation between pain intensity and disability.
Keywords: Disability; Occupational health; Dentists; Musculoskeletal disorders; Risk factors; Cumulative trauma disorders